BENTUK DAN UPAYA PENANGANAN KEKERASAN PADA ANAK - Tri Susilaningsih (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2004)
The study of violence on children is conducted based on the news issued in mass media (Jawa Pos dated on 25 March 2000), that the rate of violence on children is considerably high. In Malang, there are approximately three fatal cases of this violence happens every month and more than 300 cases has occurred in East Java for the last three years. This study aims at realizing the importance of understanding the impact of violence on children and detecting it earlier. Therefore, it is necessary to do preventive acts on it. Besides, it is also important for parents to take care of their children with great ajection in order to grant welfare to them. This study is very useful to make the awareness of laws better for children and parents to believe that doing violence on children will contribute more negative results if it is carried out.